Assessment of the incidence and risk factors of early poststroke seizures in Lebanese patients. Issue 11 (19th October 2021) - Mansour, Sara; Youness, Mahmoud; Cherri, Sarah; Salameh, Pascale; Hallit, Souheil; Malaeb, Diana; Hosseini, Hassan
Abstract: Background: Early seizures have been recognized as serious complications of ischemic strokes where the data are limited among Lebanese patients. This study aimed to assess the incidence and risk factors of early seizures postischemic stroke and to determine the effect of early seizures on functional outcome among Lebanese stroke patients. Methods: This was a retrospective observational study conducted between January 2017 and March 2020 on patients with acute ischemic strokes at two tertiary hospitals in Lebanon. Data were collected from patients' medical records at each site through a well‐designed data collection sheet. Early seizures were defined as seizures occurring within 7 days after acute stroke. Functional outcome was assessed at discharge, according to modified Rankin scale (mRS). Results: Of 140 enrolled patients, early seizure developed in 12 patients (8.6%) with mean age of 68.42 ± 9.89 years and 8 (67%) were females. Independent risk factors for early seizure development were female gender and cortical involvement. Moreover, early seizure development was not associated with higher disability and mortality at hospital discharge. Conclusion: The findings of the study highlight that early seizures occurred more commonly in patients with cortical involvement and female gender. In addition, early seizures did not impair functional outcome in our study, however; further studies are needed to predict patients at risk of early seizure so that appropriate prevention and treatment strategies can be implemented promptly. Abstract : This is a retrospective study conducted at two Lebanese hospitals and aimed to determine the incidence, the predictive factors, and the effect of early seizures on the functional outcome of Lebanese ischemic stroke patients. Of 140 enrolled patients, ES developed in 12 patients (8.6%) with female gender and cortical involvement being the most significant predictive factors for ES. Moreover, ES development was not associated with higher disability and mortality.